Pemanfaatan Sumber Daya Lingkungan Eksisting Untuk Pengembangan Potensi Wilayah Sekitar Kampus - Sugara, Ayub; Nugroho, Muhammad Nur Dita; Amrullah, Amir Husaini Karim (Fakultas Pertanian_Universitas Tidar, 2024)
Beringin Raya Village's position, near the Bengkulu University campus and directly adjacent to Central Bengkulu Regency, should allow it to flourish as a satellite area. This location has the potential to become a new hub of activity, serving as a gateway between Bengkulu City and its neighboring districts. However, the development of the area surrounding the school in Beringin Raya Village is slower than that of neighboring villages nearby. The restrictions of regional expansion in the Beringin Raya sub-district resulted in the formation of spaces between residential settlements with a high potential for agricultural, livestock, and home industry development. The agricultural and livestock sectors are not the primary economic drivers in the Beringin Raya sub-district. The realities on the ground demonstrate that some individuals earn a living as farmers, particularly vegetable and horticulture growers who work in settlements. Identification of surrounding environmental resources in Beringin Raya Village is the first step toward understanding the potential problems, possibilities, and risks that will arise in the area. Field observations and conversations with community leaders are part of the data collection process. The next stage following identification is to establish priorities. The development of the area surrounding the Bengkulu University campus is a difficult task that necessitates a collaborative approach. Various variables are interconnected and impact one another in attempts to solve existing problems. The study programs of Bengkulu University play a vital role in contributing ideas, research, devotion, and solutions to help overcome or decrease current difficulties. Collaboration with the government, stakeholders, and local communities is essential for developing and executing effective policies.